2022
DOI: 10.3389/fphys.2022.885444
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Transcriptomics Analysis Reveal the Contribution of Lungs on High-Altitude Hypoxia Adaptation in Tibetan Sheep

Abstract: The Tibetan sheep is an indigenous species on the Tibetan plateau with excellent adaptability to high-altitude hypoxia and is distributed at altitudes of 2500–5000 m. The high-altitude hypoxia adaptation of Tibetan sheep requires adaptive reshaping of multiple tissues and organs, especially the lungs. To reveal the mechanisms of adaptation at the tissue and molecular levels in the lungs of Tibetan sheep under hypoxic conditions at different altitudes, we performed light and electron microscopic observations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In addition to the genes related to early domestication, a panel of interesting genes associated with other economic traits was also revealed. These genes were previously reported in goats, sheep and other species, showing correlations with spermatogenesis and sperm motility ( KIF3B , KIF17 , KIAA0825 and TNFRSF21 ) [ 53 , 54 , 55 , 56 ], growth and development ( TNPO2 , IFT80 , UCP2 , UCP3 , GHRHR , SIM1 , CCM2L , CTNNA3 and CTNNA1 ) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], fat deposition ( ACSF3 and FGGY ) [ 65 , 66 ], chicken heat tolerance ( TSHR and SUGCT ) [ 67 ], high-altitude hypoxia adaptation ( CHL1 ) [ 68 ], milk composition ( GHRHR ) [ 69 ], milk flavour ( ACSF3 ) [ 70 ], carcass traits ( GHRHR ) [ 71 ] and hair follicle morphogenesis ( GLI2 ) [ 72 ]. The iHS and ROH methods both detected some genes, but each method found additional genes not detected by the other.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the genes related to early domestication, a panel of interesting genes associated with other economic traits was also revealed. These genes were previously reported in goats, sheep and other species, showing correlations with spermatogenesis and sperm motility ( KIF3B , KIF17 , KIAA0825 and TNFRSF21 ) [ 53 , 54 , 55 , 56 ], growth and development ( TNPO2 , IFT80 , UCP2 , UCP3 , GHRHR , SIM1 , CCM2L , CTNNA3 and CTNNA1 ) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], fat deposition ( ACSF3 and FGGY ) [ 65 , 66 ], chicken heat tolerance ( TSHR and SUGCT ) [ 67 ], high-altitude hypoxia adaptation ( CHL1 ) [ 68 ], milk composition ( GHRHR ) [ 69 ], milk flavour ( ACSF3 ) [ 70 ], carcass traits ( GHRHR ) [ 71 ] and hair follicle morphogenesis ( GLI2 ) [ 72 ]. The iHS and ROH methods both detected some genes, but each method found additional genes not detected by the other.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving pulmonary adaption to hypoxia at high altitude, Chl1 was one of the most downregulated genes, possibly modulating the enhanced ventilatory response after exposure to hypoxia. [ 78 ] These target genes are expressed in the airway epithelium, basal cells, and PNECs as shown from the LungMAP database. Furthermore, ISH studies from this study localized miR-30a in the bronchioles.…”
Section: Discussionmentioning
confidence: 99%
“…This may be closely related to the adaptation of yaks to the hypoxic environment of the plateau and reduces water consumption during respiration. At the same time, studies have shown that abundant dilated capillaries and large numbers of erythrocytes in the alveolar septa are conducive to increased alveolar ventilation and oxygen transport [51][52][53][54][55][56]. We measured the percentage of alveolar septa at all levels of the peribronchiolar alveoli in yaks after H&E, Masson, and PAS staining, observing a highly significant difference compared to that of cattle, and we also observed that the alveolar septa in yaks between adjacent alveoli was rich in capillaries, and that the number of red blood cells was higher than that of cattle.…”
Section: Discussionmentioning
confidence: 99%